2013
DOI: 10.1515/znc-2013-5-603
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects Induced by Linalool in Normotensive and Hypertensive Rats

Abstract: Linalool is a monoterpene alcohol and constituent of several Brazilian aromatic medicinal plants, popularly used against hypertension. Cardiovascular effects induced by linalool were evaluated. In normotensive rats, ()-linalool [1, 5, 10, and 20 mg/kg body weight (BW); intravenous (i.v.)]-induced hypotension was associated with tachycardia, which was attenuated by atropine (2 mg/kg BW) and N G -nitro-L-arginine methyl ester (20 mg/kg BW), but was not modifi ed after indomethacin (5 mg/kg BW) administration. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
2
21
0
7
Order By: Relevance
“…We found that neroli significantly decreased [Ca 2+ ] c and attenuated KCl-induced contraction, suggesting that neroli exerts its vasodilatory effect, at least in part, by inhibiting Ca 2+ influx. These findings are consistent with a previous study, which showed that linalool, the most abundant component of neroli, exerted an antagonizing effect on extracellular Ca 2+ -dependent contractions in mesenteric arteries [16].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that neroli significantly decreased [Ca 2+ ] c and attenuated KCl-induced contraction, suggesting that neroli exerts its vasodilatory effect, at least in part, by inhibiting Ca 2+ influx. These findings are consistent with a previous study, which showed that linalool, the most abundant component of neroli, exerted an antagonizing effect on extracellular Ca 2+ -dependent contractions in mesenteric arteries [16].…”
Section: Discussionsupporting
confidence: 94%
“…However, since ruthenium red decreases store-operated Ca 2+ entry [21], it is more likely that neroli inhibits a RyR-dependent, storeoperated Ca 2+ entry pathway rather than directly affecting intracellular Ca 2+ release. Neroli essential oil and its main components, commonly used in foods and as a natural complement to standard therapies, are known to exert relaxation effects [16]. Mixed essential oils that contain neroli essential oils have been reported to decrease diastolic blood pressure in hypertensive subjects [22].…”
Section: Discussionmentioning
confidence: 99%
“…LIN induced vasodilation in a dose‐dependent manner, a property associated with endothelial function. The finding that LIN dose‐dependently induced vasorelaxation is consistent with previous results showing that the vasorelaxant effect of LIN was not influenced by endothelium [15]. This study used mouse aortae, which are capacitance blood vessels, whereas the previous study used rat mesenteric arteries, which are resistance blood vessels.…”
Section: Discussionsupporting
confidence: 90%
“…The effects of reducing BP were attributed to decrease in level of vascular tone factor II (angiotensin II; Chai, Tian, Li, Liu, & Wu, 2010). It has been revealed that treatment of normotensive and hypertensive rats with linalool (a compound in celery) caused the reduction of BP through the dilation of vascular smooth muscle (Anjos et al, 2013). Su et al demonstrated the antihypertensive effects of luteolin (a substance in celery) in spontaneous hypertensive rats in vivo models.…”
Section: Effects On Hypertensionmentioning
confidence: 99%